Buprenorphine dosing choices in specific populations: review of expert opinion. (1st September 2016) - Maremmani, Icro; Rolland, Benjamin; Somaini, Lorenzo; Roncero, Carlos; Reimer, Jens; Wright, Nat; Littlewood, Richard; Krajci, Peter; Alho, Hannu; D'Agnone, Oscar; Simon, Nicolas
ABSTRACT: Introduction : Treatment of opioid dependence with buprenorphine improves outcomes. Typical dosing ranges for all patients from clinical evidence and as defined in the product information are wide. For specific groups with complex clinical scenarios, there is no clear consensus on dosing choices to achieve best possible outcomes. Areas covered : The doses of buprenorphine used in 6 European countries was reviewed. A review of published evidence supported rapid induction with buprenorphine and the benefits of higher doses but did not identify clearly useful guidance on dosing choices for groups with complex clinical scenarios. An expert group of physicians with experience in addiction care participated in a discussion meeting to share clinical practice experience and develop a consensus on dosing choices. Expert opinion : There was general agreement that treatment outcomes can be improved by optimising buprenorphine doses in specific subgroups. Specific groups in whom buprenorphine doses may be too low and who could have better outcomes with optimised dosing were identified on the basis of clinical practice experience. These groups include people with severe addiction, high tolerance to opioids, and psychiatric comorbidities. In these groups it is recommended to review dosing choices to ensure buprenorphine dosing is sufficient.